Direct detection of the psychoactive substance MT‐45 in human tissue samples by probe electrospray ionization‐tandem mass spectrometry. Issue 6 (3rd May 2018) - Usui, Kiyotaka; Murata, Tasuku; Fujita, Yuji; Kamijo, Yoshito; Hanazawa, Tomoki; Yoshizawa, Tomohiro; Funayama, Masato
Abstract: Analyses of drugs and poisons in tissue samples are essential in forensic toxicology and pharmacology. However, current procedures for tissue analysis are laborious and time‐consuming. Therefore, we assessed the utility of a newly devised probe electrospray ionization (PESI) technique with tandem mass spectrometry (MS/MS) for easy, ultra‐rapid drug detection in human tissue samples. Using this system, typical pretreatment procedures, such as solid‐phase extraction, liquid–liquid extraction, deproteinization, or homogenization, can be avoided. Briefly, a tissue sample of 1–2 mm 3 was supplemented with a solution of ethanol and 10 mmol/L ammonium formate, and measurements were obtained. We demonstrated the successful application of this method in a forensic case by detecting an opioid analgesic, MT‐45, in all tissue samples (liver, kidney, lung, brain, and heart). We also detected oxidized metabolites of MT‐45 in the liver. Since the analysis required only 0.5 minutes per sample, PESI–MS/MS is an ultra‐rapid detection method. Furthermore, for a quantitative approach, the total analysis time for the combination of PESI–MS/MS with the quick, easy, cheap, effective, rugged, and safe (QuEChERS) extraction method (from instrument start‐up to extraction and PESI‐analysis) was within 8 minutes. MT‐45 concentrations obtained by QuEChERS–PESI–MS/MS and liquid chromatography (LC) –MS/MS were similar for all tissue samples. PESI–MS/MS cannot be used to separate isobars/isomers (ie, compounds with the same m/z value), similar to other direct introduction techniques. Further studies are needed to validate the quantitation method. However, our results indicate that PESI–MS/MS is a potentially easy and rapid technique for the analysis of drugs and poisons in human tissue samples.